Vaccine-induced protection against gastrointestinal bacterial infections in the absence of secretory antibodies - Simmons, Cameron (2018)
Secretory IgA (SIgA) is widely held to be responsible for the defense of the mucosae against pathogenics and other potentially harmful agents. In this study, polymeric Ig receptor (pIgR) knockout mice, which lack secretory antibodies (SAb), were used to investigate the role of vaccine-elicited SAb in protection against gastrointestinal bacterial infections. An essential role for specific SAb in protection against Vibrio cholerae was evident from experiments showing that vaccinated pIgR(-/-) mice, but not vaccinated C57BL/6 mice, were susceptible to cholera toxin challenge. Vaccination of C57BL/6 mice with Salmonella typhimurium elicited strong antigen-specific, mucosal responses, which blocked in vitro invasion of epithelia. However, vaccinated C57BL/6 and pIgR(-/-) mice were equally resistant to challenge infection with virulent S. typhimurium. Finally, we investigated the importance of SIgA in protection against recurrent infections with Citrobacter rodentium. Although higher numbers of bacteria were detected early after challenge infection in feces of vaccinated pIgR(-/-) mice compared with vaccinated C57BL/6 mice, both mouse strains showed complete clearance after 9 days. These results suggested that, in immune animals, SIgA is crucial for the protection of gastrointestinal surfaces against secreted bacterial toxins, may inhibit early colonization by C. rodentium, but is not essential for protection against re-infection with S. typhimurium or C. rodentium.